Anomalous Quality of Service Deterioration at Roundabouts Caused by Rainfall - Ben Edigbe, Johnnie Ebioye; Ibijola, Stephen (Promet - Traffic&Transportation, 2019)
The paper investigated the extent to which rainfall influences the quality of service delivery at multilane roundabouts using a novel quality of service approach. Quality of service is defined as how well roundabouts operate based on road users and road providers’ perception of service quality. Delay and reserve capacity were used respectively as proxies for road users and road providers’ perception of service quality. The entry and circulating traffic data were recorded continuously for eight weeks under dry, light, moderate, and heavy rainfall weather conditions at each surveyed roundabout, then collated, analysed and compared. Linear regression with dummy variable was used to model the roundabout entry capacity and a corrector factor was added to modify the regression function. The corrector factor considered different entry radii and entry angles of surveyed roundabouts. Multi-criteria quality of service table with travel time as proxy for road users and speed as proxy for road providers’ perception of service delivery was developed from peak traffic data and used to determine the extent of deterioration. The multi-criteria table introduced in the paper is a clear departure from the speed-based criteria used in many studies. The results show a significant increase in time delay and a decrease in reserve capacity relative to rainfall. The paper has concluded that rainfall has an anomalous negative effect on the quality of service at multilane roundabouts. The findings could be used in a variety of ways in traffic management to predict the travel time at roundabouts under rainy conditions and to prescribe speed limits accordingly.